2022
DOI: 10.4049/jimmunol.2100981
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-Derived Prostaglandin E2 Drives IL-1–Independent Mycobacterium bovis Bacille Calmette-Guérin–Triggered Skin Dendritic Cell Migration to Draining Lymph Node

Abstract: Inoculation of Mycobacterium bovis Bacille Calmette-Guérin (BCG) in the skin mobilizes local dendritic cells (DC) to the draining lymph node (dLN) in a process that remains incompletely understood. In this study, a mouse model of BCG skin infection was used to investigate mechanisms of skin DC migration to dLNs. We found enhanced transcription of cyclooxygenase (COX)-2 and production of COX-derived PGE 2 early after BCG infection in skin. Animals treated with antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Some researchers were concerned that suppression of PGD2 could potentially impact the antiinflammatory action of nicotinic acid, such as PGD2induced inhibition of antigen-presenting Dendritic Cells (DC) activation in inflammation (VanHorn et al, 2012). A study involving mouse models has demonstrated that shortterm administration of niacin can suppress the retention of DC in lymph nodes and that this effect is not abolished by naproxen-induced suppression of prostaglandin generation (Krmeska et al, 2022). Furthermore, another in vitro experiment in human monocytes has clearly shown that the anti-inflammatory action of niacin was not affected by PGD2 inhibition, as evidenced by the measurements of 352 TNF-α, MCP1 and interleukin 6 (Giri et al, 2019).…”
Section: Non-lipoprotein-related Effects Of Niacinmentioning
confidence: 99%
“…Some researchers were concerned that suppression of PGD2 could potentially impact the antiinflammatory action of nicotinic acid, such as PGD2induced inhibition of antigen-presenting Dendritic Cells (DC) activation in inflammation (VanHorn et al, 2012). A study involving mouse models has demonstrated that shortterm administration of niacin can suppress the retention of DC in lymph nodes and that this effect is not abolished by naproxen-induced suppression of prostaglandin generation (Krmeska et al, 2022). Furthermore, another in vitro experiment in human monocytes has clearly shown that the anti-inflammatory action of niacin was not affected by PGD2 inhibition, as evidenced by the measurements of 352 TNF-α, MCP1 and interleukin 6 (Giri et al, 2019).…”
Section: Non-lipoprotein-related Effects Of Niacinmentioning
confidence: 99%
“…In mouse models, BCG dose can easily range from 5 × 10 5 to 10 7 colony‐forming units (CFUs) independent of the route of administration. For instance, in our research we have routinely worked with 1–2 × 10 6 CFUs of BCG injected in the footpad skin, ear dermis, or i.v 2,14–17 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, in our research we have routinely worked with 1-2 × 10 6 CFUs of BCG injected in the footpad skin, ear dermis, or i.v. 2,[14][15][16][17] Prior work on the implications of BCG dose on immune responses has mostly focused on protection against M. tuberculosis challenge, while the more immediate, immunological reactions unleashed by escalating BCG dose in vivo are largely uncharacterized. In the current study, we used a mouse model of BCG skin infection to investigate the early events that unfold in the LN draining the BCG injection site in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…The murine counterpart of human CD1c + mDCs - CD11b + cDCs - initiate Th1 T cell immunity during pulmonary Mtb infection ( Lai et al., 2018 ). Moreover, migratory epidermal CD11b hi cDCs transport BCG from the skin to draining LN to prime CD4 + T cells following BCG inoculation ( Bollampalli et al., 2015 ; Krmeska et al., 2022 ). Human blood-derived CD1c + mDCs are susceptible to infection with BCG, up-regulating CD40, CCR7, HLA-DR, CD86 and other maturation markers, as well as producing TNF-α and IL-6 ( Lozza et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%